Correlations Among Nutritional Status and Physical Activity in Relation to Physical Fitness Levels of University Students in Indonesia: A Comprehensive Literature Review - Kurniawati, Yusfita; Nevangga, Rizky Patria; Bakti, Ananda Perwira; Rachman, Dwi Ariawan Tauhid; Sahani, Kandilia (Journal of Unified Multidisciplinary Practice in Sports, Health, and Medicine, 2026)
This study aims to explore the relationship between nutritional status and physical activity on the physical fitness levels of Indonesian university students using a literature review method. The study utilized electronic databases from Google Scholar and Garuda, with a time frame limited to the past five years. The keywords used for article searches included nutritional intake, nutritional status, physical activity, physical fitness, VO2max, and university students. The inclusion criteria established were physical fitness assessments based on muscle strength and endurance, cardiovascular endurance, flexibility, agility, speed, and VO2max, as well as questionnaires/interviews, university students from all universities in Indonesia, and articles published within the last five years. The exclusion criterion was the inaccessibility of the full-text article. From the database search, 10 articles met the inclusion and exclusion criteria. Based on the analysis, the findings concluded that nutritional status and physical activity have a significant relationship with the physical fitness levels of university students in Indonesia. Students with a balanced nutritional status, sufficient macronutrient intake, and lower fat consumption tend to have higher physical fitness levels. Regular physical activity also plays an essential role in improving physical fitness and overall health. This study recommends implementing healthy lifestyle programs in academic environments and conducting further research on factors influencing physical fitness levels.